The Influencer as a Political Subject: The Case of Maruri and Logan Y Logan During Guillermo Lasso's Presidential Campaign - Acosta Corral, Monserrat; Sánchez Jánosik, Zsofia (Ius Humani. Jornal do direito, 2024)
Social Networks have dictated the shift from traditional politics to present-day politics, impacting the development of political campaigns where influences have erected themselves as a relevant actor. This political subject has been mainly studied from a marketing and communication point of view leaving aside its role as subject-action in politics. Therefore, the goal of this research is to study the role of the influencer during Guillermo Lasso's 2021 presidential campaign from an analytical perspective of politics simplification. Our methodology is qualitative and interpretive in nature. We analyze the digital content created by two local influencers: Eduardo Maruri and Logan y Logan. In the first part of our analysis we characterize the influencer in the context of the political campaign. In the second part, we expose the space that the influencer occupies within the society of spectacle and immediacy. In the same way, we show the strategies that emerged from the commercialization of political content and the influencer's image. Finally, we address the function of assimilation and concretion of information in the digital content of TikTok and Instagram linked to the campaign. This investigation shows the role of the influencer as a simplifier of reality through the use of entertaining and simple media content which embed themselves in the logic of social media platforms, which they use to generate engagement with their followers, challenging their emotions and influencing their behavior and decision making.